2012
DOI: 10.3109/13651501.2012.667111
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D, parathyroid hormone, serum calcium and phosphorus in patients with schizophrenia and major depression

Abstract: The findings suggest that vitamin D affects the brain independent of hormonal pathways which regulate serum level of calcium. Non-significant difference in the serum level of vitamin D between the schizophrenics and the depressed patients suggests that the independent effect of vitamin D in brain is a general effect and is not specialized to a specific region or pathway in the brain; however, differences between psychiatric and non-psychiatric patients might be resulted from differences in psychosocial backgro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(23 citation statements)
references
References 21 publications
3
17
1
Order By: Relevance
“…This first finding is in contrast to earlier case-control studies including patients with established psychotic disorders (Rey-Sanchez et al, 2009;Partti et al, 2010;Itzhaky et al, 2012;Jamilian et al, 2013). These previous studies however have methodological limitations, including lack of adjustment for ethnicity (Rey-Sanchez et al, 2009;Partti et al, 2010;Doknic et al, 2011;Jamilian et al, 2013), comparison between hospitalized patients and health care workers (Itzhaky et al, 2012) or hospitalized patients and healthy controls recruited by advertisements without control for place of residence (Crews et al, 2013).…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…This first finding is in contrast to earlier case-control studies including patients with established psychotic disorders (Rey-Sanchez et al, 2009;Partti et al, 2010;Itzhaky et al, 2012;Jamilian et al, 2013). These previous studies however have methodological limitations, including lack of adjustment for ethnicity (Rey-Sanchez et al, 2009;Partti et al, 2010;Doknic et al, 2011;Jamilian et al, 2013), comparison between hospitalized patients and health care workers (Itzhaky et al, 2012) or hospitalized patients and healthy controls recruited by advertisements without control for place of residence (Crews et al, 2013).…”
Section: Discussioncontrasting
confidence: 52%
“…These previous studies however have methodological limitations, including lack of adjustment for ethnicity (Rey-Sanchez et al, 2009;Partti et al, 2010;Doknic et al, 2011;Jamilian et al, 2013), comparison between hospitalized patients and health care workers (Itzhaky et al, 2012) or hospitalized patients and healthy controls recruited by advertisements without control for place of residence (Crews et al, 2013). The healthy controls in the current study were randomly recruited from the same catchment area as the study patients and matched both for ethnicity and other important confounding variables such as gender and age.…”
Section: Discussionmentioning
confidence: 98%
“…In fact, Lebanon is located at appropriate latitudes (33° 35'N) [38] for the synthesis of vitamin D [39] and thus, higher levels of total vitamin D would be expected [39]. Furthermore, our results indicated that patients with schizophrenia, as well as the healthy ones, had a vitamin D deficiency, similar to previous studies [2,4,36,37,40,41]. Other studies conducted in Lebanon had shown a hypovitaminosis D in the healthy population [35,[42][43][44][45].…”
Section: Discussionsupporting
confidence: 80%
“…A meta-analysis, including 19 studies (2804 participants), showed a strong association between vitamin D deficiency and schizophrenia [2], with 65% of them being vitamin D deficient [2]. Other studies [6,36,37] showed that adults with schizophrenia have significantly lower serum concentrations of vitamin D as compared with healthy controls. It was expected that vitamin D levels in the Lebanese population would be higher due to the sunny climate.…”
Section: Discussionmentioning
confidence: 99%
“…A number of epidemiological studies have found associations between serum 25(OH)D concentrations and depression, independent of lifestyle and health factors (Ganji et al, 5 Wendy H. Oddy 2010; Hoang et al, 2011;Jamilian et al, 2013;Kjaergaard et al, 2011;Lee et al, 2011;Milaneschi et al, 2010;Tolppanen et al, 2012). However, others have shown no association, including a large population-based study in the United States (Nanri et al, 2009;Pan et al, 2009;Zhao et al, 2010).…”
Section: Introductionmentioning
confidence: 97%